Worry about victimization: an alternative and reliable measure for fear of crime - Williams, Franklin P. (Western criminology review, 2000)
The concept of fear of crime has generated substantial interest within criminology. While discussions of what fear of crime means, and what dimensions are represented by fear of crime, have become commonplace, actual measurement issues have only recently gained attention. This article questions the utility of fear as a concept and argues for "worry" about crime as a more reasonable substitute. We convert various commonly-used measures of fear to worry and compare their dimensions and reliability. A victimization-based worry scale is developed as part of this comparison and generates the most crime-focused measurement, as well as the highest reliability measures. The scale may have greater utility for measuring specific concerns about crime than existing approaches using fear of crime.